Trade prospects for developing countries - Balassa, Bela A.; Economic Growth Centre (Homewood, Ill., R. D. Irwin, 1964)
This volume presents the results of an inquiry into the trade prospects of the developing countries in the period up to 1975.The projections of the study are conditional forecasts because they depend on a set of assumptions.
includes list of abbreviations
Includes bibliographies.
ijb 15/01/2019
Loans
Keywords: Commerce; International trade; International economic relations; Developing countries